2020
DOI: 10.1002/mds.28401
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Guidelines on Rodent Models of Restless Legs Syndrome

Abstract: Restless legs syndrome (RLS) is a chronic sensorimotor disorder diagnosed by clinical symptoms. It is challenging to translate the diagnostic self‐reported features of RLS to animals. To help researchers design their experiments, a task force was convened to develop consensus guidelines for experimental readouts in RLS animal models. The RLS clinical diagnostic criteria were used as a starting point. After soliciting additional important clinical features of RLS, a consensus set of methods and outcome measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Our findings reinforce the importance of studies analyzing iron levels periodically and other mechanisms of possible alterations. Even with the recommendation of the task force (Salminen et al, 2021) in carrying out the experiments on RLS rodent models of both sexes, this is a limitation in our study, since it was not possible to analyze the estrous cycle phase and the hormonal fluctuations, both potential confounders to be taken into account. However, studies indicate pregnancy has a major impact on the risk of developing RLS for those with a family history of RLS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings reinforce the importance of studies analyzing iron levels periodically and other mechanisms of possible alterations. Even with the recommendation of the task force (Salminen et al, 2021) in carrying out the experiments on RLS rodent models of both sexes, this is a limitation in our study, since it was not possible to analyze the estrous cycle phase and the hormonal fluctuations, both potential confounders to be taken into account. However, studies indicate pregnancy has a major impact on the risk of developing RLS for those with a family history of RLS.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the iron supplementation diet during pregnancy showed an influence on the increased freezing of offspring. This suggests that the animals that underwent the 8-week training (regardless of diet) and the offspring of the supplementation groups (OSu) experience a lower need to move, which represents a reduction in the core feature of RLS, which is the need for movement (Salminen et al, 2021). Despite studies show changes in fear and anxiety behavior due to fetal iron deficiency (Beard et al, 2002;Texel et al,2012), in the present study, we found no differences in grooming and in time spent in the center between time spent along the walls in the open-field test that report anxious behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Following the compilation of the IRLSSG consensus guidelines on rodent models of RLS ( Salminen et al, 2021 ), the IRLSSG Executive Committee approved a motion in October 2020 that the previously appointed animal models task force continue its work and assess the construct validity of potential RLS models. Twelve of the original 14 members undertook this work.…”
Section: Methods Used To Determine Rls Models With Construct Validitymentioning
confidence: 99%
“…Addressing this issue is particularly challenging when developing animal models of RLS with face validity , that is, animal models that closely reproduce the clinical features of human RLS. The challenge of defining parameters for rodent models of RLS with face validity was recently addressed by a task force convened by the International Restless Legs Syndrome Study Group (IRLSSG) ( Salminen et al, 2021 ).
Box 1. International RLS Study Group (IRLSSG) consensus diagnostic criteria for RLS Essential diagnostic criteria: The urge to move the legs usually but not always accompanied by, or felt to be caused by, uncomfortable and unpleasant sensations in the legs.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation